Dynamic and isometric protocols of knee extension: Effect of fatigue on the EMG signal - Dias da Silva, S. R. [UNESP]; Gonçalves, Mauro [UNESP] (My University, 2006)
The objective of this study was to analyze the electromyographic (EMG) signal behavior of rectus femoris (RF), vastus medialis (VM), vastus lateralis (VL) and biceps femoris (caput longum) (BFCL) from nine women during fatiguing dynamic and isometric knee extensions tests and to determine their EMGFT (Electromyographic Fatigue Threshold). Surface electrodes, biological signal acquisition module, analogical-digital converter board and specific software were used. The RMS (Root Mean Square) values obtained from concentric phase (80 to 30 degrees) of the dynamic knee extension andfrom isometric contraction were correlated with time on each load by linear regression analysis. The respective slopes were correlated with the correspondent load to determine the EMGFT. Force (Kgf) and median frequency - MF (Hz) obtained during MIVC (Maximal Isometric Voluntary Contraction) performed before and after the fatiguing tests were calculated in Matlab environment. The results demonstrated that the endurance time decreases with higher loads the EMG amplitude increase with time and was greater at higher loads, between muscles in dynamic exercise the RF and VL showed higher slopes, and in isometric exercise the VL showed the same behavior The EMGFT values were similar in both exercises; the force values predominantly decreased after fatiguing tests; however the MF only decreased after some loads. The protocols proposed allowed standardizing protocols at least to induce the fatigue process and to determine the EMGFT as an endurance indicative, which may be used to evaluate the effectiveness of rehabilitative or training interventions indicated to reduce muscle weakness and fatigue.
Keywords: Dynamic contraction; Electromyography; Isometric contraction; Knee; Muscle fatigue; adult; analog digital converter; biceps femoris muscle; calculation; clinical protocol; computer program; controlled study; correlation analysis; display system; dynamic exercise; dynamics; electrode; electromyogram; endurance; female; human; human experiment; knee; leg movement; leg muscle; muscle fatigue; muscle force; muscle isometric contraction; muscle training; muscle weakness; normal human; rectus femoris muscle; rehabilitation; signal processor; standardization; statistical analysis; vastus lateralis muscle; weight bearing; Adolescent; Adult; Female; Humans; Muscle Contraction; Muscle Fatigue; Quadriceps Muscle; Reference Values; Weight-Bearing